Peran Kepala Sekolah dalam Mengoptimalkan Kemampuan Guru untuk Mengembangkan Tujuan Pembelajaran Berdasarkan Kebutuhan Siswa di SMPN 2 Golewa - Maria Imaculata Bhoki (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This study aims to analyze the role of school principals in enhancing teacher competencies to design learning objectives aligned with student needs at SMPN 2 Golewa. The research utilized the School Action Research method, conducted in three cycles. The subjects consisted of 10 teachers requiring support in designing differentiated learning objectives. Data were collected through observation, interviews, and documentation, and analyzed qualitatively and quantitatively. The findings revealed significant improvements in the quality of lesson plans (RPP), average student evaluation scores, and student participation. The quality of lesson plans increased from an average score of 2.9 in the pre-cycle to 4.2 in the second cycle. Average student evaluation scores rose from 65.3 to 78.4, while student participation improved from 57% to 76.5%. Principal support through training, supervision, and reflection proved effective in enhancing teachers’ ability to design learning aligned with the Merdeka Curriculum. This study recommends regular training, teacher collaboration, and continuous monitoring to support teacher professional development. The findings are expected to serve as a reference for implementing school leadership that fosters differentiated learning.